2000
DOI: 10.1097/00007890-200012270-00005
|View full text |Cite
|
Sign up to set email alerts
|

Increased Level of Hsp27 but Not of Hsp72 in Human Heart Allografts in Relation to Acute Rejection1

Abstract: For the first time in humans with cardiac allograft rejection, increased expression of HSP27, which could be important for cardiac self-protection, was demonstrated. For the lack of increased HSP72 expression, the influence of the cyclosporine A treatment was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Taken together, these results strongly suggest vascular expression of HSP27 is associated with freedom from CAV. It has been previously reported that HSP27 is diffusely expressed by cardiac myocytes of transplanted hearts, 13 but blood vessels were not investigated. Little is known about expression of HSP27 in normal and diseased human blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results strongly suggest vascular expression of HSP27 is associated with freedom from CAV. It has been previously reported that HSP27 is diffusely expressed by cardiac myocytes of transplanted hearts, 13 but blood vessels were not investigated. Little is known about expression of HSP27 in normal and diseased human blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of Hsp27 were found in cardiac biopsy specimens associated with acute rejection after transplantation, but its cellular effects are uncertain. (13) Late after transplantation also, Hsp27 expression in vessels was found to correlate with freedom from cardiac allograft vasculopathy after cardiac transplantation. (11)…”
Section: Discussionmentioning
confidence: 99%
“…(10) The smaller heat shock proteins have been less investigated as source of alloimmunity, but Hsp27 expression has been correlated with allograft rejection after cardiac and renal transplantation. (1113) However, the research as of now does not clearly indicate whether the increased expression of Hsps is a cytoprotective result of the cellular stress induced by transplantation or whether the increased expression is an antigenic stimulus eliciting allograft rejection.…”
mentioning
confidence: 99%
“…Heat shock protein-27 is constitutively expressed in human cardiomyocytes ( 7 ), and ex vivo studies using mouse hearts overexpressing Hsp-27 have demonstrated that it protects the myocardium against ischemia and reperfusion injury ( 8, 9 ). Further studies have demonstrated that Hsp-27 is expressed within human blood vessels ( 10 ) and phosphorylated Hsp-27 is believed to be protective against atherosclerosis ( 1012 ).…”
mentioning
confidence: 99%